Heat shock protein 70–2 (HSP70-2) is a novel therapeutic target for colorectal cancer and is associated with tumor growth. Issue 1 (December 2016) - Jagadish, Nirmala; Parashar, Deepak; Gupta, Namita; Agarwal, Sumit; Suri, Vaishali; Kumar, Rajive; Suri, Vitusha; Sadasukhi, Trilok; Gupta, Anju; Ansari, Abdul; Lohiya, Nirmal; Suri, Anil
Abstract Background Colorectal cancer (CRC) is the third leading cause of cancer related deaths worldwide both in men and women. Our recent studies have indicated an association of heat shock protein 70–2 (HSP70-2) with bladder urothelial carcinoma. In the present study, we investigated the association of HSP70-2 with various malignant properties of colorectal cancer cells and clinic-pathological features of CRC in clinical specimens. Methods HSP70-2 mRNA and protein was investigated expression by RT-PCR, immunohistochemistry, immunofluorescence, flow cytometry and Western blotting in CRC clinical specimens and COLO205 and HCT116 cell lines. Plasmid-based gene silencing approach was employed to study the association of HSP70-2 with various malignant properties of COLO205 and HCT116 cells in in vitro and with tumor progression in in vivo COLO205 human xenograft mice model. Results HSP70-2 expression was detected in 78 % of CRC patients irrespective of various stages and grades by RT-PCR and IHC. Our analysis further revealed that HSP70-2 expression was detected in both COLO205 and HCT116 cell lines. Ablation of HSP70-2 expression resulted in reduced cellular growth, colony forming ability, migratory and invasive ability of CRC cells. In addition, ablation of HSP70-2 expression showed significant reduction in tumor growth in COLO205 human xenograft in in vivo mouse model. Conclusion Collectively, our results indicate that HSP70-2 is associated with CRC clinical specimens. In addition, down regulation of HSP70-2 expression reduces cellular proliferation and tumor growth indicating that HSP70-2 may be a potential therapeutic target for CRC treatment.